Pengaruh Kemampuan Manajerial dan Budaya Organisasi Terhadap Mutasi Kerja dan Dampaknya Terhadap Kinerja Karyawan PT. Bank Sultra - Ahmad Hamid, Wiwin Sultraeni; Jacob Breemer (Jurnal Ilmu Sosial Dan Pendidikan, 2024)
This research intent for:1 ) manajerial's ability Influence chairman of to job mutation on PT. Sultra Bank. 2 ) manajerial's ability Influence chairman of for performance to fire an employee on PT. Sultra Bank. 3 ) Influence culturize organizations to job mutation on PT. Sultra Bank. 4 ) Influence culturize organizations for performance to fire an employee on PT. Sultra Bank. 5 ) job mutation Influences for performance to fire an employee on PT. Sultra Bank On this research observational variable consisting of   a ) manajerial's ability. b). Organisational culture, c ) job mutation and d.) performance fires an employee. Analisis who is utilized is statistical description and analisis path (analisis is band). Research results many for example conclusion first conclusion, manajerial's ability having contribution having for signifikan to job mutation fires an employee PT. South-east Sulawesi Region development bank  Unaaha's Branch office, Assistants Branch office Asera and Assistant Branch Office Punggaluku . Both of, manajerial's ability having contribution having for signifikan for performance to fire an employee PT. Sultra Bank  Unaaha's Branch office, Assistants Branch office Asera and Assistant Branch Office Punggaluku . Third, Organisational culture having contribution having for signifikan to job mutation fires an employee PT. Sultra Bank  Unaaha's Branch office, Assistants Branch office Asera and Assistant Branch Office Punggaluku . Fourth, Organisational culture having contribution having for signifikan for performance to fire an employee PT. Sultra Bank  Unaaha's Branch office, Assistants Branch office Asera and Assistant Branch Office Punggaluku . To five,  Job mutation have signifikan's ascendant contribution for performance to fire an employee PT. Sultra Bank.